Serum Osteocalcin, Sclerostin and Lipocalin-2 Levels in Adolescent Boys with Obesity over a 12-Week Sprint Interval Training - Marit Salus; Vallo Tillmann; Liina Remmel; Eve Unt; Evelin Mäestu; Ülle Parm; Agnes Mägi; Maie Tali; Jaak Jürimäe (MDPI AG, 2023)
The aim of the study was to examine the effects of supervised cycling sprint interval training (SIT) on serum osteocalcin, lipocalin-2 and sclerostin levels, and bone mineral characteristics among obese adolescent boys. Untrained obese adolescent boys aged 13.4 ± 0.3 were assigned to either a 12-week SIT group (3 sessions/week), or a non-exercising control group who continued with their habitual everyday life. Serum osteocalcin, lipocalin-2 and sclerostin concentrations, and bone mineral values were assessed before and after intervention. After 12-week intervention, where 14 boys in both groups ended the study, there were no significant differences in serum osteokine levels between the groups after 12 weeks, while whole body bone mineral content and lower limb bone mineral density increased in the SIT group (p < 0.05). Change in body mass index was negatively correlated with the change in osteocalcin (r = −0.57; p = 0.034), and positively correlated with the change in lipocalin-2 levels (r = 0.57; p = 0.035) in the SIT group. Supervised 12-week SIT intervention improved bone mineral characteristics, but did not change osteocalcin, lipocalin-2 or sclerostin levels in adolescent boys with obesity.